Catalytic asymmetric addition of diorganozinc reagents to N-phosphinoylalkylimines - Côté, Alexandre (National Academy of Sciences, 2004)
The synthesis of α-chiral amines bearing two alkyl groups has been hampered by the accessibility and stability of the alkylimine precursor. Herein, we report an efficient strategy to generate the alkyl-substituted imine in situ that is compatible with the Me-DuPHOS monoxide·Cu(I) catalyzed addition of diorganozinc reagents. The sulfinic acid adduct of the imine is readily prepared by mixing diphenylphosphinic amide, the aldehyde, and sulfinic acid. The sulfinic acid adduct is generally isolated by filtration. The addition of diorganozinc reagents in the presence of Me-DuPHOS monoxide·Cu(I) and the in situ-generated imines affords the corresponding α-chiral amines in high yields and enantiomeric excesses.